Efficacy of Warm Water Compress and Aloe Vera Therapy for Fever Management in Preschoolers: A Study at Cempaka High Care Unit, Dr. Moewardi Hospital - Oktaviana, Putri; Prajayanti, Eska Dwi; Ratrinaningsih, Suciana (Jurnal Kesehatan Komunitas Indonesia, 2025)
Background: Hyperthermia is a condition that often occurs in preschool children due to infection or inflammation. If not treated immediately, hyperthermia can cause complications such as dehydration and febrile seizures. One safe and effective non-pharmacological method is warm water compresses, which help lower body temperature by increasing heat evaporation and stimulating vasodilation, thereby improving blood circulation. Objective: This study aims to determine the effectiveness of warm water compresses in lowering body temperature in preschool children with hyperthermia in the Cempaka High Care Unit of Dr. Moewardi Hospital, Surakarta. Method: This study used a descriptive case study method on two children with hyperthermia. Body temperature was measured before and after giving warm water compresses for 15-20 minutes every 4 hours. Results: Child Patient S's body temperature decreased from 39.0°C to 36.4°C and Child Patient M's from 38.2°C to 36.2°C within 24-48 hours after the intervention. Conclusion: Warm water compresses have been proven effective, safe, and simple as a non-pharmacological method in lowering the body temperature of preschool children.